Implementation of Character Education Based on Religious Local Wisdom to Develop Students' Morality - Muhisom Muhisom; Rima Yuni Saputri (Assyfa Journal of Islamic Studies, 2026)
The moral decline occurring among students is currently becoming increasingly widespread. This is evidenced by the rising cases of student brawls, free sex, cheating habits, and so forth. Therefore, the education sector in Indonesia must continue to improve and seek solutions to these problems. One way to address issues related to student moral decline is through the implementation of character education based on religious local wisdom in schools. This study aims to analyze the implementation of character education based on religious local wisdom and its implications for the moral development of students at MTs Darul A'mal Metro. This research uses a qualitative approach. Data collection techniques in this study were conducted through observation, interviews, and documentation. The results show that the implementation of character education is carried out through religious activities, skills development, extracurriculars, and character habituation. The implications of implementing this character education include strengthening religious identity, forming morals based on Islamic values, increasing tolerance, social awareness, and preventing deviant behavior. Thus, character education based on religious local wisdom has proven effective in developing students' morals.